The journeys of trees : a story about forests, people, and the future - St George, Zach (W.W. Norton & Company, 2020)
"An eye-opening investigation into forest migration past and present-and the people fighting to save its uncertain future. Forests are restless. Any time a tree dies or a new one sprouts, the forest that includes it has shifted. Today, however, an array of obstacles-humans felling trees by the billions, invasive pests transported through global trade-threaten to overwhelm these vital movements. Worst of all, the climate is changing faster than ever before, and forests are struggling to keep up. A deft blend of science reporting and travel writing, The Journeys of Trees examines the evolving movements of forests by focusing on five types of tree: giant sequoia, ash, black spruce, Florida torreya, and Monterey pine. Journalist Zach St. George reads fossils that show the paths of ancient forests, introduces lively characters on the conservation front lines-such as an ecologist studying droughts and an evolutionary evangelist with plans to save a dying species-and reveals how we can all help our trees, and our planet, survive and thrive"--